Distance Protection for Electrical Transmission Line: Equipments, Settings Zones and Tele-Protection - M. Zellagui; A. Chaghi (Saarbrücken - Allemagne, 2012)
<dl> Power System Protection is the art and science of the application of devices that monitor the power line currents and voltages (relays) and generate signals to deenergize faulted sections of the power network by circuit breakers. Goal is to minimize damage to equipment and property that would be caused by system faults, if residues, and maintain the delivery of electrical energy to the consumers. Many types of protective relays are used to protect power system equipments, they are classified according to their operating principles; over current relay senses the extra (more than set) current considered dangerous to a given equipment, differential relays compare in and out currents of a protected equipment, while impedance relays measure the impedance of the protected piece of planet. For a good performance of a relay in a power system it must have the following characteristics; dependability, security, selectivity, sensitivity and speed. Protective relaying is a vital part of any electric power system: unnecessary during normal operation but very important during trouble, faults, and abnormal disturbances. </dl>